2006
DOI: 10.1007/s00415-006-0218-8
|View full text |Cite
|
Sign up to set email alerts
|

Low dose treatment with the synthetic cannabinoid Nabilone significantly reduces spasticity-related pain

Abstract: About 30% of patients with chronic upper motor neuron syndrome (UMNS) suffer from disabling spasticity-related pain not sufficiently correctable by conventional treatment. Delta9-tetrahydrocannabinol (Delta(9)-THC) was reported to add benefit in the treatment of pain in patients with multiple sclerosis (MS). The question arose whether synthetic cannabinoids with lower potential for psychotropic side effects could be effective as well. To evaluate the safety and efficacy of low dose treatment with the synthetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
126
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(129 citation statements)
references
References 30 publications
1
126
0
2
Order By: Relevance
“…Such pharmaceuticals include dronabinol and nabilone, which are prescribed as antiemetics and appetite stimulants to patients afflicted with the AIDS wasting syndrome or receiving cancer chemotherapy (Mechoulam and Hanus, 2000). Nabilone is also used as an adjunct therapy for the management of chronic pain associated with fibromyalgia and multiple sclerosis (Wissel et al, 2006;Skrabek et al, 2008). The true potential of the cannabinoid-based agents as potential therapeutics became more apparent after the cloning of the receptors for ⌬ 9 -THC (Matsuda et al, 1990;Munro et al, 1993).…”
Section: A Marijuana and Cannabinoidsmentioning
confidence: 99%
“…Such pharmaceuticals include dronabinol and nabilone, which are prescribed as antiemetics and appetite stimulants to patients afflicted with the AIDS wasting syndrome or receiving cancer chemotherapy (Mechoulam and Hanus, 2000). Nabilone is also used as an adjunct therapy for the management of chronic pain associated with fibromyalgia and multiple sclerosis (Wissel et al, 2006;Skrabek et al, 2008). The true potential of the cannabinoid-based agents as potential therapeutics became more apparent after the cloning of the receptors for ⌬ 9 -THC (Matsuda et al, 1990;Munro et al, 1993).…”
Section: A Marijuana and Cannabinoidsmentioning
confidence: 99%
“…Recently, preliminary guidelines also give knowledge about the use of smoked cannabis (84). Synthetic cannabinoid such as nabilone (1 mg/day) decreased spasticity related pain without much of these adverse effects (85). Further, adjuvant effects of 10 and 20 mg doses of dronabinol were also observed in patients with chronic pain who are under opioid therapy (86).…”
Section: Cannabinoidsmentioning
confidence: 80%
“…Cannabinoids are used to treat a variety of nervous system conditions (Wissel et al, 2006;Notcutt, 2015). Many ongoing trials on a diverse range of cannabinoids have shown them to be beneficial for epilepsy (Cunha et al, 1980;Wallace et al, 2001); however, other studies have shown that cannabis can have variable effects on seizures in different species (Meldrum et al, 1974;Martin and Consroe, 1976;Chiu et al, 1979).…”
Section: Discussionmentioning
confidence: 99%